New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae) - Hu, Jia-Yao; Pan, Zhao-Hui (Zootaxa, 2018)
A new species of Nazeris Fauvel, 1873 from Xizang, China, is described and illustrated: N. zhifeii Hu & Pan, sp. n. A key to Nazeris species in Xizang and a map showing their distribution are given.